2010
DOI: 10.4103/0019-5545.64588
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of dementia under the aegis of mental health program, Maharashtra, Pune chapter

Abstract: Background:There has been an exponential growth in the number of elderly population in India. This study aims to determine the prevalence of dementia in an urban center of Pune and to evaluate the corresponding socio-demographic correlates along with psychiatric morbidity in the study sample.Materials and Methods:The study population in Pune and Kirkee cantonments was selected based on 2001 census data. The number of people over 65 years numbered 6721 and 2145 of them were randomly selected for a door-to-door … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…13 This instrument consists of 20 items with 7-point Likert scale that ranged from 'strongly disagree' to 'strongly agree' to reveal nursing students' attitudes toward dementia in two sub-domains namely "dementia knowledge' ( items 3,7,10,11,12,14,15,18,19,20) and "social comfort" (items 1,2,4,5,6,8,9,13,16,17) with good psychometric properties (Cronbach's alpha 0.83-0.85). Points ranging from 1 to 7 were given to each response such that the more positive the response, the higher the score.…”
Section: The Attitude Toward Alzheimer's Disease Andmentioning
confidence: 99%
“…13 This instrument consists of 20 items with 7-point Likert scale that ranged from 'strongly disagree' to 'strongly agree' to reveal nursing students' attitudes toward dementia in two sub-domains namely "dementia knowledge' ( items 3,7,10,11,12,14,15,18,19,20) and "social comfort" (items 1,2,4,5,6,8,9,13,16,17) with good psychometric properties (Cronbach's alpha 0.83-0.85). Points ranging from 1 to 7 were given to each response such that the more positive the response, the higher the score.…”
Section: The Attitude Toward Alzheimer's Disease Andmentioning
confidence: 99%
“…A community based survey in Pune, India yielded a prevalence rate 4.1%. 12 A study in a rural community in Kerala showed a prevalence of 33.9 per 1000 in people aged 60 years and above. 13 Compared to this study, a western study showed a higher prevalence rate (9.8%).…”
Section: Discussionmentioning
confidence: 99%
“…They showed a positive correlation between low levels of education with an increased incidence of dementia. 14 Data from the Assets and Health Dynamics of the Oldest Old (AHEAD) study in the U.S. showed a relationship between higher education and better maintenance of cognitive function and indicated that those with low levels of education were more likely to become cognitively impaired. 15 A recent study in New York found that lower educational level was associated with a higher risk of dementia.…”
Section: Discussionmentioning
confidence: 99%